Development of a multifaceted (MECSUS) protocol in the search for novel bioactive entities from microorganisms / Rasha Saad Abd Elgadir Soliman - Abd Elgadir Soliman, Rasha Saad Abd Elgadir Soliman (Institute of Graduate Studies, UiTM, 2013)
The advent of new chemical genetic tools and high-throughput screening technologies and platforms have already led and will continue to lead in accessing the natural product diversity of microorganisms. This thesis represents a continuation of the work on the investigation into means of making better use of the advantages of new technologies and the OSMAC approach (One Strain Many Compounds) in drug discovery that the Atta-ur-Rahman Research Institute of Natural Product Discovery (RiND) at MARA University of Technology has engaged in. The result of this thesis is the MECSUS (Microtiter plate, Elicitors, Combination, Solid phase extraction, UHPLC, Statistical analysis) protocol. It involves miniaturized parallel fermentations in 96-well microtiter plate with up to ninety six different media, parallel extraction of the supernatant layer of the fungus via a polymer based solid phase extraction (SPE) plate, chromatographic assessment of the results via UHPLC, and multivariate analysis of the chromatograms…